2022
DOI: 10.1021/acssuschemeng.2c03437
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Needle in a Haystack: Producing Antimicrobial Cutin-Derived Oligomers from Tomato Pomace

Abstract: Agro-industrial residues comprise a rich diversity of plant polymers and bioactive compounds, constituting promising sources for the development of materials, including bioplastics, and food supplements, among other applications. In particular, the polyester cutin is abundant in fruit peel, a plentiful constituent of pomace agro-industrial residues. The potential of diverse fruit pomaces as a source for the development of cutin-derived materials/products has been extensively sought out. This study expands the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Cutin was purified from tomato pomace since its high availability as an agroindustry residue (European Commission, 2021) enables the production of large amounts of polymeric structures. Moreover, previous studies showed that cutin purified with an ionic liquid from tomato pomace (consisting of peels, seeds and stems) is virtually similar to that obtained from the tomato peel fraction alone (Escórcio et al, 2022).…”
Section: Cutin Polymer Activates a Ros Burst In Arabidopsismentioning
confidence: 82%
See 3 more Smart Citations
“…Cutin was purified from tomato pomace since its high availability as an agroindustry residue (European Commission, 2021) enables the production of large amounts of polymeric structures. Moreover, previous studies showed that cutin purified with an ionic liquid from tomato pomace (consisting of peels, seeds and stems) is virtually similar to that obtained from the tomato peel fraction alone (Escórcio et al, 2022).…”
Section: Cutin Polymer Activates a Ros Burst In Arabidopsismentioning
confidence: 82%
“…S2). Cutin hydrolysates, which are obtained by an extensive hydrolysis of the cutin, consist almost exclusively of aliphatic monomers with a few aromatic monomers (Escórcio et al, 2022). These hydrolysates also did not elicit a ROS burst (Fig.…”
Section: Cutin Polymer Activates a Ros Burst In Arabidopsismentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, tomato cuticles are rich in cutin polyester, whose monomer composition is highly homogeneous (tomato cutin mainly consists of 9(10)-16 dihydroxyhexadecanoic acid). Tomato pomace is currently the largest and growing source of cutin-rich wastes, ranging from 6 to 9.10 6 tons per year. After separation from seeds and pulp, tomato peels, containing more than 60% cutin, can be hydrolyzed by alkali treatment to yield fatty acid extracts containing mostly 9(10)-16 dihydroxyhexadecanoic acid with typically less than 10% of impurities such as α,ω-dicarboxylic fatty acids and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%